New Approaches in Media and Communication - Ayhan, Ahmet (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
With the emergence of new media technologies, communication practices are changing, and this book aims at offering new insights into these digital media communication practices, featuring contributions by researchers from various disciplines. With a collection of chapters on a wide range of topics in the field of communication and media, this edited book offers its readers to comprehend the current situation of the new media and communication practices in Turkey through the researches carried out using the surveys, interviews, and content analyses, as well as through a comprehensive analysis of the media sector in the new media age. The readers will find the international perspective of quite a number of academics to the phenomenon of new media and its effects, outcomes, and future trends.
Keywords: digitální spojovací systémy; digitální média; mediální komunikace; sociální komunikace; digital communications; digital media; communication in mass media; communication; elektronické knihy; electronic books